Spiritualism Seeks Sword for Self Defense Konark, World Heritage Site: Hieroglyphics – Katha - Bhattacharya, Deepak (Historical Journal, 2023)
Hindu adhyatmais ‘consciousness about the soul, its perimeter (time & space), purpose, practices & prognosis’. It is not an ism (dogma). It is a way of life. The Hindu scholar is termed a ‘Brahmana’. Pan globally and historically, scholars are known as incapable of physical combat & self-defense; require extra mural physical protection. Post the fall of Constantinople (c. 1453 A.D.) to the Jihadists, Islam (peaceful) went murderously viral (The Thesis), and became Muslim (sequestering).The Hindus (riparian beings) in sub-continent India were slaughtered; homesteads, women & livelihoods were taken away; worship & ritual places were done to dust or converted. Faced with barbarians, an existential crisis had arisen out of such historical processes. The docile imid (kafir) spiritual Brahmans (scholar) had then opted for the mace, muscle, sword, and shield (Anti-Thesis). The ecclesiastical system was maintained side-by-side (Synthesis). The UNESCO world heritage site of Konarak (c.13th A.D., Odisa, India,) has artifacts informing the beholder via hieroglyphics that the then state had played such role quite tellingly, took pride in the might of arms, pomp, in proclaiming defense at of the invader; protection of the erudite; and the gamp seeker. Sanatan survived. Data & discussions about any such military counter have remained due. First time. Nascent attempt. Theoretical history about such complex process paths. Non-revisionist.